Inquérito soro-epidemiológico da dengue na Regional VI de Fortaleza - Ceará, no período entre outubro de 2013 a abril de 2014 - Pires, Camila de Lizier Mesquita (2015)
Dengue is an arbovirose considered to be a major public health problem, especially in intertropical regions. In 2012, Fortaleza recorded the largest dengue epidemic in its history, with the introduction of the dengue virus 4 (DENV-4), with more than 35,000 confirmed cases and with an expressive lethality. Currently, the prevalence of dengue in the population of Fortaleza is unknown, since the last seroepidemiological survey was conducted in 1994, when only serotypes 1 and 2 had been isolated and at the time the prevalence was 44%. The present study aims to determine the seroprevalence of dengue in Region VI of the city of Fortaleza in the year 2013, to evaluate this seroprevalence and to determine its distribution in this population. A sample corresponding to 19 census tracts was drawn to estimate a prevalence of 60%, with a relative error of 10%, and a 95% confidence interval. From these sectors, 380 participants were randomly selected, which had serum samples collected for testing using the qualitative enzyme immunoassay method marketed by Virion® Serion®. The prevalence of carriers of anti-dengue IgG antibodies was 67.36%. Seropositivity was more frequent among female subjects (45.26%), possibly due to the longer stay of the female in the in-home or peridomiciliary environment, and in the age group of individuals ≥ 40 years (32.89%), an indicative that the longer the exposure period of the individual to the vector, the greater the chances of dengue infection. Individuals with elementary education (32.36%) presented higher seropositivity, which suggests a correlation between schooling and lack of knowledge of preventive measures in the fight against the vector. Among the people who reported not having had dengue before, 50.79% had positive serology, which suggests the presence of asymptomatic infections, or symptomatic bias. The presence of a higher positivity (45.26%) in individuals with income less than or equal to 2 minimum wages suggests a greater transmission of dengue in the less economically favored classes. The disagreement of the present study with other surveys can be explained by the fact that some surveys use data obtained from the disease notification system, which registers more popular classes seeking medical care in public services, unlike the present survey, which refers to a serological survey of a random population sample, which may justify its results being more coherent on the actual dispersion of the dengue virus.